Experimental analysis of single-phase cycloconverter for resistive loads with submultiples of frequencies - Calsina, Helarf (2024)
This article is developed due to the need to have electrical power with adjustable frequencies, different from that supplied by the conventional electrical network, for industrial and motor control applications. The implemented cycloconverter consists of a power stage with SCR devices and optocouplers, a control stage with a microcontroller for managing the trigger signals of the power semiconductors. Simulations and experimental tests were carried out to validate the operation of the system under various conditions. The cycloconverter can effectively modify the 60Hz input frequency, providing adjustable and stable output frequencies for resistive loads. The results show experimental frequencies very close to those calculated: for a submultiple of 2, 29.976 Hz; submultiple of 3, 20 Hz; submultiple of 4, 15Hz, submultiple of 5, 11.99 Hz; and for a submultiple of 6.10 Hz. The minimum variations between the simulated and experimentally obtained frequencies are due to tolerance factors of the electronic components. This proposed method is of practical importance to improve the application level of cycloconverter in speed control of AC drives.